THE USE OF SCHEMA ACTIVATION STRATEGY FOR TEACHING WRITING RECOUNT TEXT - Griselda, Jessica; Sutapa, Gatot; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The purpose of this research was to find out whether or not the schema activation strategy increase students? writing skill of recount text on the tenth grade students of SMA Negeri 8 Pontianak. The form of this research was a Pre-Experimental design by using single group pre-test and post-test design. The population of the research is the tenth grade students of SMA Negeri 8 Pontianak consisted of 312 students. From the population, the sample class X MIA 4 is taken randomly with 39 students. The result of t-test obtains 6.03 that is bigger than t-table 1.6860. If the obtained t result is bigger (or equal to) the critical t-value, then the null hypothesis is rejected. It means that increasing the students? skill in writing recount text through the use of schema activation indicates a significance different result between the pre-test and post-test. The use of schema activation strategy for teaching writing recount text succeeded in increasing students? writing text. The students? writing score was improved and students can write recount text well and enjoyed in learning English writing. Keywords : Schema Activation Strategy, Writing, Recount Text   Abstrak: Penelitian ini bertujuan untuk menemukan apakah strategi aktivasi skema meningkatkan keterampilan menulis teks recount siswa kelas sepuluh SMA Negeri 8 Pontianak atau tidak. Bentuk dari penelitian ini adalah desain Pre-Eksperimen atau desain grup tunggal pre-test dan post-test. Populasi penelitian ini adalah siswa kelas sepuluh SMA Negeri 8 Pontianak yang terdiri dari 312 siswa. Dari populasi ini, kelas X MIA 4 diambil secara acak sebagai sample yang berjumlah 39 siswa. Hasil t-test mencapai nilai 6.03 dimana lebih besar dari t-table 1.6860. Penggunaan strategi aktivasi skema untuk mengajar menulis teks recount berhasil meningkatkan keterampilan menulis siswa. Nilai menulis siswa meningkat dan siswa dapat menulis teks recount dengan baik dan menikmati pelajaran menulis dalam Bahasa Inggris. Kata Kunci: Strategi Aktivasi Skema, Penulisan, Teks Recount